2021
DOI: 10.3390/microorganisms9061141
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Micro-Evolutionary Features of Mammalian 2 orthobornavirus (Variegated Squirrel Bornavirus 1, VSBV-1)

Abstract: Mammalian 2 orthobornavirus (VSBV-1) is an emerging zoonotic pathogen discovered in several exotic squirrel species and associated with fatal human encephalitis. The dynamics of VSBV-1 spread and evolution in its presumed natural hosts are unknown. Here, we present the phylogeny, micro-evolution, cross-species transmission and spread of VSBV-1 at a temporal and spatial resolution within the limits of animal husbandry. The results showed that VSBV-1 can be classified into six distinct groups and that the most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The evolutionary rates of nucleotide substitution in the analyzed genotypes belonging to Orthobornavirus alphapsittaciforme showed similar ranges between the nucleoprotein and the matrix, aligning with the evolutionary rates of other Mononegavirales [48,49], including other bornaviruses [46,50]. It was estimated that the time to the most recent common ancestor (TMRCA) of the entire species dates to the beginning of the 11th century, while genotypes 4 and 2, which are currently the most prevalent, would have originated in the mid-17th and mid-18th centuries, respectively.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The evolutionary rates of nucleotide substitution in the analyzed genotypes belonging to Orthobornavirus alphapsittaciforme showed similar ranges between the nucleoprotein and the matrix, aligning with the evolutionary rates of other Mononegavirales [48,49], including other bornaviruses [46,50]. It was estimated that the time to the most recent common ancestor (TMRCA) of the entire species dates to the beginning of the 11th century, while genotypes 4 and 2, which are currently the most prevalent, would have originated in the mid-17th and mid-18th centuries, respectively.…”
Section: Discussionsupporting
confidence: 64%
“…The survival and adaptation of the virus in a specific environment are influenced by mechanisms of selective pressure, which can be either biotic or abiotic. Few studies have detected signs of selective pressure in Orthobornaviruses [ 45 , 46 ]. In our study, we observed the presence of sites undergoing episodic diversifying selection in both the N and M genes.…”
Section: Discussionmentioning
confidence: 99%